The expression of PI3K/AKT signal pathway in breast tissue and it’s clinical significance - Gang, Z; Xiao-meng, L; Jun-hua, Z; Yong, C; Xing, Z (Journal of Chitwan Medical College, 2017)
This work aimed to investigate the expression of p-AKT in breast tissue and its clinical significance. Methods: Western blot and RT-PCR were used to detect the expression of p-AKT in 100 cases of breast cancer and 30 cases of normal breast tissue. The expression levels of p-AKT in breast cancer were significant higher than that in normal breast tissue. The expressions of p-AKT had correlation with Clinical grade(P<0.05), but it was irrelevant to the age, tumor size, lymph node metastasis and histological differentiating degree. PI3K/AKT Signal Pathway may take a part in the development and progression of breast cancer.